Pengaruh Habit Dan Trust Dalam Minat Menggunakan ShopeePay Pada Pembelanjaan Online (Studi Kasus Pada Aplikasi Shopee) - Ardianti Nurinda Aprillia; Tetty Rimenda (Account : Jurnal Akuntansi, Keuangan dan Perbankan, 2022)
The development of the times created a variety of very sophisticated information technology. One of them is a payment method that can now be non-cash or Cashless. ShopeePay is an electronic money service feature that is used as a non-cash payment method on the Shopee application. The purpose of this study is to determine whether the Habit and Trust factors can affect consumer interest in using ShopeePay for online shopping. The Habit factor is examined to determine whether Shopee users are familiar or not in using ShopeePay. In addition, the Trust factor is used in this study because to decide to buy online and use cashless, many things must be considered, one of which is trust. This study uses primary data by distributing online questionnaires and has obtained 100 respondents. With the respondent criteria needed are ShopeePay users in online shopping, domiciled in DKI Jakarta, aged at least 17 years to more than 45 years. Data analysis in this study used regression analysis. The results show that the Habit and Trust factors have a significant effect on interest in using ShopeePay for online shopping. Consumers are accustomed to using ShopeePay because of the online shopping routines that tend to be frequent, according to the results of consumer research using Shopeepay for the last 1-2 years. And consumers trust that ShopeePay can maintain its reputation, have a good quality website and become a competent and honest company. Trust grows because Shopee and ShopeePay are able to provide payment security guarantees for consumers. Based on age characteristics, this research is dominated by users 17-22 years old who are gen Z who were born with developed technology so they are familiar with online transactions. Keywords: Interest in Using, Online Shopping, ShopeePay